A Safe Interaction of Robot Assisted Rehabilitation, Based on Model-Free Impedance Control with Singularity Avoidance - Iman Sharifi; Ali Doustmohammadi; Heidar Ali Talebi (IAES International Journal of Robotics and Automation (IJRA), 2015)
In this paper, a singularity-free control methodology for the safe robot-human interaction is proposed using a hybrid control technique in robotic rehabilitation applications. With the use of max-plus algebra, a hybrid controller is designed to guarantee feasible robot motion in the vicinity of the kinematic singularities or going through and staying at the singular configuration. The approach taken in this paper is based on model-free impedance control and hence does not require any information about the model except the upper bounds on the system matrix. The stability of the approach is investigated using multiple Lyapunov function theory. The proposed control algorithm is applied to PUMA 560 robot arm, a six-axis industrial robot. The results demonstrate the validity of the proposed control scheme.